2014
DOI: 10.1186/1752-4458-8-33
|View full text |Cite
|
Sign up to set email alerts
|

How can a change in the operating system of the mental health review board promote the discharge of long-term hospitalized psychiatric patients? A case study of Seoul city

Abstract: BackgroundOne of the most typical and chronic problem in Korean mental health system is the prolonged length of hospital stay. In contrast to there are many components which leads to long length of stay of psychiatric patients in Korean situation such as low and fixed medical fee for psychiatric inpatient treatment, shortage of community resources, lack of care-givers’ awareness and so on, there are just few mechanisms to handle this issue such as Mental Health Review Board (MHRB) which is based on Mental Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…A study on the early implementation of the Mental Health (Care and Treatment) (Scotland) Act 2003 found that half of the informants felt that the outcome of their tribunal hearing was a ‘foregone conclusion’ and that tribunal outcomes that deviated from individuals' preferences undermined valuable mechanisms – such as advance statements, the named person provision and independent advocacy – which were designed to enhance participation (Ridley & Hunter, ). The inability of individuals to shape tribunal outcomes was also evident in a survey with mental health review board members in South Korea, where individuals and carers' wishes were not factored into the tribunal's decision‐making deliberations (Lee, Lim, Kim, & Lee, ).…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on the early implementation of the Mental Health (Care and Treatment) (Scotland) Act 2003 found that half of the informants felt that the outcome of their tribunal hearing was a ‘foregone conclusion’ and that tribunal outcomes that deviated from individuals' preferences undermined valuable mechanisms – such as advance statements, the named person provision and independent advocacy – which were designed to enhance participation (Ridley & Hunter, ). The inability of individuals to shape tribunal outcomes was also evident in a survey with mental health review board members in South Korea, where individuals and carers' wishes were not factored into the tribunal's decision‐making deliberations (Lee, Lim, Kim, & Lee, ).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Individuals are thus perceived as being unnecessarily held in hospital in several jurisdictions. For instance, in a South Korean study, 93% of respondents stated that it would be difficult to discharge somebody whose mental health had stabilised but who lacked appropriate supports in the community (Lee et al, ). Similarly, slightly under a quarter of probate judges in South Caroline indicated that a lack of alternatives would increase the chances of granting an order (Ferlauto & Frierson, ).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…In Korea, mental health services are typically characterized by low accessibility to psychiatric treatment, high caseloads, and a relatively large incidence of inpatient care 11. The duration of untreated psychosis (DUP), which is related to a poor prognosis for patients with schizophrenia,1213 is comparatively long in Korea relative to that of Western countries14 and may be attributed to the high level of stigma associated with psychosis and psychiatric treatment 15.…”
Section: Introductionmentioning
confidence: 99%